PERANAN LATIHAN OLAHRAGA TERHADAP PERKEMBANGAN OTAK - Sukadiyanto . (LPMPP Universitas Negeri Yogyakarta, 2004)
A number ofphysical activities are classified as sports. Sport exercises give somebenefits to the people actively and physically involved. RegullIT exercise in such act.as walking, jogging, swimming, and playing games like'temUs, football, and badmintonis associated withbetterphysical and mental fitness. Sport exercises get people ready to avoid manymajordiseases and to live healthier, less stressful, and more productive lives than those led bypeople who live sedentary lives. Whenhealth is somehow absent, all the technological advances are useless. Thus there is a direct link between participation inregularphysical activity and good health. Sport exercises prepare people for lifelong health. It is indeed true that such exercises can very much help those with physical and mental problems. Such exercises are good for the body and the brain because the motion ofthe body influences the mind. Physical fitness is not only one ofthe most important keys to a healthy bodybut also the basis ofdynamic and creative intellectual activity. Intelligence and skill could only function at the peak of their capacity when the body is strong. Hardy spirits and tough mindsusually inhabit soundbodies. Sport exercises mayalso enhance neurotransmitter activity in the brain and increase oxygen transport to the brain: By means ofsport exercises people gain opportlmities to develop all their intelligence, whether it is bodily-kinesthetic, spatial, interpersonal, intrapersonal, musical, linguistic, logicalmathematical, of nati.rraJ.istic. . .' - One ofthe amazing fuets to come out ofall the recent research is that the same amount ofexercise helps both the physical selfand the brain. Inessence, this article merely points out what we have already strongly suspected people have experienced: sport exercises are good for both the body and the brain. Through regular, active use ofthe body, one can discover a greater sense ofwell-being, far greater vi tality, and a calmer, more relaxed attitude toward daily pressures. Keywords: sport exercises, brain